2016
DOI: 10.1590/0103-6440201601166
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Head Position on Maxillofacial Transverse Measurements Made on the Skull and Cone Beam Computed Tomography Scans

Abstract: Article Incorrect patient positioning and the resultant image distortion occur in many radiographic examinations. This study aimed to assess the effect of tilting, rotation and tipping of the head on the accuracy of maxillofacial transverse measurements made on cone beam computed tomography (CBCT) scans. The CBCT scans were obtained in central position of 10 dry human skulls. Using three-dimensional (3D) Dolphin software, six positions namely 10° and 20° tilts, rotations and tips were reconstructed of central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…The results of studies carried out by (Adibi et al, 2017;Almeida et al, 2021;Kakumoto et al, 2021;Shokri et al, 2016) regarding the accuracy of linear measurements confirmed the present findings. In line with the present results, Tolentino et al (Tolentino et al, 2018) performed linear measurements on CBCT scans with three different voxel sizes using three different software programs.…”
Section: Discussionsupporting
confidence: 90%
“…The results of studies carried out by (Adibi et al, 2017;Almeida et al, 2021;Kakumoto et al, 2021;Shokri et al, 2016) regarding the accuracy of linear measurements confirmed the present findings. In line with the present results, Tolentino et al (Tolentino et al, 2018) performed linear measurements on CBCT scans with three different voxel sizes using three different software programs.…”
Section: Discussionsupporting
confidence: 90%